2017
DOI: 10.1094/pdis-03-17-0352-re
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Fungicide Sensitivity of Colletotrichum Species Complexes from Rubber Tree in Hainan, China

Abstract: Colletotrichum gloeosporioides and C. acutatum species complexes are causal agents of Colletotrichum leaf disease (CLD) of rubber trees worldwide. To determine the geographic distribution of Colletotrichum species complexes associated with CLD of rubber trees in Hainan, China, and their sensitivity to fungicides used in the region, a total of 275 Colletotrichum isolates were collected from 52 rubber tree plantations in 11 counties. These isolates were identified based jointly on morphological characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A recent study also indicated that the C . gloeosporioides species complex is the dominant species complex in rubber tree in Hainan (Cao et al ., ). The compositions of Colletotrichum species differ in different regions and coffee varieties, and a large‐scale survey is needed to confirm this differential distribution.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…A recent study also indicated that the C . gloeosporioides species complex is the dominant species complex in rubber tree in Hainan (Cao et al ., ). The compositions of Colletotrichum species differ in different regions and coffee varieties, and a large‐scale survey is needed to confirm this differential distribution.…”
Section: Discussionmentioning
confidence: 97%
“…Responses to common commercial fungicides vary among Colletotrichum species (Cao et al ., ). The present results confirmed this variable sensitivity to fungicides among Colletotrichum isolates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…High control efficacy of DIF has been reported in several ascomycetes such as Phacidiopycnis spp., Venturia inaequalis, Colletotrichum spp., Marssonina coronaria, Alternaria spp., and Fusarium spp. ( Munkvold and O’Mara, 2002 ; Villani et al, 2015 ; Fonseka and Gudmestad, 2016 ; Cao et al, 2017 ; Dang et al, 2017 ; Ali et al, 2018 ) and the basidiomycete Rhizoctonia solani ( Bartholomäus et al, 2017 ). Given the widespread occurrence of resistance to two of the three current postharvest fungicides and the stringent limitations to new postharvest fungicides registration, DIF could be a valuable additional tool to manage blue mold of pome fruit in the years to come if used appropriately and if its efficacy against other major postharvest diseases is proven.…”
Section: Discussionmentioning
confidence: 99%